Surgical ablation of atrial fibrillation using energy sources - Brick, Alexandre Visconti (2015)
Surgical ablation, concomitant with other operations, is an option for treatment in patients with chronic atrial fibrillation. The aim of this study is to present a literature review on surgical ablation of atrial fibrillation in patients undergoing cardiac surgery, considering energy sources and return to sinus rhythm. A comprehensive survey was performed in the literature on surgical ablation of atrial fibrillation considering energy sources, sample size, study type, outcome (early and late), and return to sinus rhythm. Analyzing studies with immediate results (n=5), the percentage of return to sinus rhythm ranged from 73% to 96%, while those with long-term results (n=20) (from 12 months on) ranged from 62% to 97.7%. In both of them, there was subsequent clinical improvement of patients who underwent ablation, regardless of the energy source used. Surgical ablation of atrial fibrillation is essential for the treatment of this arrhythmia. With current technology, it may be minimally invasive, making it mandatory to perform a procedure in an attempt to revert to sinus rhythm in patients requiring heart surgery.